Acidification behavior of mixtures of pork meat and wet texturized plant proteins in a minced model system. Issue 4 (8th March 2022) - Ebert, Sandra; Michel, Wiebke; Gotzmann, Lisa; Baune, Marie‐Christin; Terjung, Nino; Gibis, Monika; Weiss, Jochen
Abstract : Abstract: The increasing use of wet texturized plant proteins as meat substitutes requires a characterization of their functional properties, especially in terms of pH‐behavior when being mixed with meat proteins to create so‐called hybrid products. In this study, a minced model system containing pork meat, curing salt, and various amounts (0–100 wt%) of wet extruded proteins from pea (Pea I, II), pumpkin (Pumpkin I, II, III), and sunflower was used to evaluate the effect of mixing on pH and time‐dependent pH‐changes upon the addition of glucono‐delta‐lactone (GDL). Increasing concentrations of plant extrudates resulted in a linear increase of the initial (pH0h ), intermediate (pH6h ), and final pH48h for all samples and higher slopes at higher native pH of extrudates were found. Acidification kinetics of all samples were similar with a distinct pH‐drop by 0.3 to 0.8 pH‐units per wt% GDL in the first 6 h, followed by a plateau where pH remained constant. At extrudate concentrations of 5 wt% (Pea I, II, Pumpkin I, II) or 15 wt% (Pumpkin III, Sunflower), a sufficient acidification with typically used GDL‐amounts ( = 1 wt%) could be achieved, while higher plant protein contents required higher GDL‐concentrations in order to reach a pH value of 5.0; a common target value in dry‐cured sausages. A mathematical model was proposed to correlate pH, time, acidifier, extrudate concentration, and plant protein origin, to aid in the adjustment of dry‐cured hybrid meat formulations, and to describe thresholds of the feasible extrudate and acidifier concentrations. Practical Application: Despite the increasing relevance of texturized plant proteins as meat mimetics, little is known about their functional and process‐related properties. This study shows that plant protein origin, the level of meat replacement, and the amount of acidifier are linked to the time‐dependent pH‐value on the basis of a mathematical model. This brings food developers one step closer in creating tailored formulations and estimating the effects of these novel ingredients in the final product characteristics of hybrid meats and analogues.